2011
DOI: 10.1007/s11295-011-0391-5
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide diversity and linkage disequilibrium in Populus nigra cinnamyl alcohol dehydrogenase (CAD4) gene

Abstract: Cinnamyl alcohol dehydrogenase (CAD) is involved in the biosynthesis of lignin, a component of plant cell wall which negatively impacts paper pulp processing and biomass fermentation to ethanol. Transgenic poplars with depressed CAD activity show structural alterations of lignin. Natural CAD mutants have been identified in several plants; however, no natural CAD mutants have been identified in poplar. We surveyed the natural genetic variation in CAD4, a gene coding for CAD, in 360 poplar trees from Western Eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
142
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(145 citation statements)
references
References 51 publications
1
142
2
Order By: Relevance
“…The comparison suggested that these candidate genes may have a similar pattern of genetic variance in the natural populations of P. tomentosa. Compared with other species within the genus Populus, the nucleotide diversity at the PtoCesA3 in our study was notably higher than that in P. trichocarpa (p T = 0.0018; Gilchrist et al 2006), P. tremula (p T = 0.0042; Ingvarsson et al 2008), P. balsamifera (p T = 0.0028, Olson et al 2010), and P. nigra (p T = 0.0012, Marroni et al 2011). The variation in nucleotide diversity detected among Populus species may be due to many factors, such as demographic history, differences in sampling or genetic background, recombination rate, gene conversion, or selection intensity (Olson et al 2010;Zhang et al 2011).…”
Section: Nucleotide Diversity and Linkage Disequilibrium In Ptocesa3contrasting
confidence: 68%
“…The comparison suggested that these candidate genes may have a similar pattern of genetic variance in the natural populations of P. tomentosa. Compared with other species within the genus Populus, the nucleotide diversity at the PtoCesA3 in our study was notably higher than that in P. trichocarpa (p T = 0.0018; Gilchrist et al 2006), P. tremula (p T = 0.0042; Ingvarsson et al 2008), P. balsamifera (p T = 0.0028, Olson et al 2010), and P. nigra (p T = 0.0012, Marroni et al 2011). The variation in nucleotide diversity detected among Populus species may be due to many factors, such as demographic history, differences in sampling or genetic background, recombination rate, gene conversion, or selection intensity (Olson et al 2010;Zhang et al 2011).…”
Section: Nucleotide Diversity and Linkage Disequilibrium In Ptocesa3contrasting
confidence: 68%
“…This result suggests the action of purifying selection on exonic regions is directly linked to the primary structure of the protein. Compared with previous reports on other genes detected in forest tree species, the nucleotide diversity (π was 0.00622) of L. olgensis was higher than that of CAD4 (π was 0.0012) in Populus nigra and nine different genes (π was 0.0018)in Populus trichocarpa [21,43], somewhat lower than that of PtoCesA7 (π was 0.0091) [44] and PtGA20Ox (π was 0.0099) [45], and similar to that of PtACT1 (π was 0.0079) [35] and PtCOBL4 (π was 0.0080) [46]. This suggested that a similar pattern of genetic variance exists in LoCAD, similar to the candidate genes in Populus.…”
Section: Nucleotide Diversity In L Olgensiscontrasting
confidence: 87%
“…The consensus sequence GD(X)9,10C(X)2C(X)2C(X)7C for binding the Zn-2 metal ion is preserved in LoCAD. In addition, 12 amino acids have been identified as substrate-binding residues in the bona fide CADs of various plant species [20,21,[37][38][39][40]. Among the CAD in L. olgensis, LoCAD contains nine of these 12 conserved residues.…”
Section: Identification and Phylogenetic Analysis Of Locadmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed variations in LD measures (D′ → 1, r 2 → 0) may be explained by low MAF of the lead SNP (Marroni et al 2011; Muller 2004; Hedrick and Kumar 2001). We took advantage of the larger FamHS data, compared the unconditional model (rs3768725 only) against conditional model (rs3768725 and rs6544903) using a likelihood ratio test, and found support for partial dependence of rs3768725 on rs6544903 (χ 2 = 4.1, df = 1, p = 0.04; data not shown in Results).…”
Section: Discussionmentioning
confidence: 95%